Long-term urology outcomes of anorectal malformation. Issue 2 (April 2022) - Chong, Clara; Hamza, Yaser; Tan, Yew Wei; Paul, Anu; Garriboli, Massimo; Wright, Anne J; Olsburgh, Jonathon; Taylor, Claire; Sinha, Manish D.; Mishra, Pankaj; Taghizadeh, Arash
Summary: Introduction: Urological problems are a recognised feature of anorectal malformation (ARM). Previous assumptions of favourable long-term urinary outcomes are being challenged. Objective: We hypothesised that urinary tract problems are common in ARM and frequently persist into adulthood. We retrospectively reviewed long-term renal and bladder outcomes in ARM patients. Study design: Patients with ARM born between 1984–2005 were identified from electronic hospital databases. Their case notes were reviewed. Renal outcomes included serum creatinine and the need for renal replacement therapy. Bladder outcomes included symptom review, bladder medication, need for intermittent catheterisation, videourodynamics and whether the patient had undergone augmentation cystoplasty. Result (Table 1 ): The case notes of 50 patients were reviewed. The median age at last follow up was 18 years (range 12–34 years). The level of fistula was noted to be high in 17 patients, intermediate in eight, and low in 10. Four had cloaca. Congenital urological abnormalities were present in 25 (50%). An abnormal spinal cord was present in 22 (44%) patients. VACTERL association occurred in 27 (54%). Chronic kidney disease stage II or above was found in 14 (28%) patients, of whom four required a renal transplant. Abnormal bladder outcomes were found in 39 (78%) patients. Augmentation cystoplasty with Mitrofanoff had been performed in 12. Of those who had not undergone cystoplasty, 17 had urinary symptoms, including urinary incontinence in 12. Of the 39 patients with abnormal bladder outcome, 19 (49%) did not have a spinal cord abnormality. There was no significant statistical association between level of ARM and abnormal renal outcome or presence of bladder abnormality. Discussion: Adverse renal and bladder outcomes are common in our cohort of young people with ARM with a significantly higher incidence compared with current literature. We did not demonstrate an association between level of ARM or presence of spinal cord anomaly with persistent bladder problems. Congenital urological anomalies are more common in those who later have an abnormal renal outcome. Although this difference is statistically significant, one fifth of patients born with anatomically normal upper tracts develop reduced renal function, implying an important acquired component. Conclusion: Bladder problems and reduced renal function affect a significant proportion of young adults with ARM. Neither adverse outcome is reliably predicted from ARM level, congenital urological anomaly or spinal cord anomaly. We advise continued long-term bladder and kidney follow-up for all patients with ARM.